Metabolic changes in aging humans: current evidence and therapeutic strategies - Palmer, Allyson K.; Jensen, Michael D. (The Journal of clinical investigation, 2022)
Aging and metabolism are inextricably linked, and many age-related changes in body composition, including increased central adiposity and sarcopenia, have underpinnings in fundamental aging processes. These age-related changes are further exacerbated by a sedentary lifestyle and can be in part prevented by maintenance of activity with aging. Here we explore the age-related changes seen in individual metabolic tissues - adipose, muscle, and liver - as well as globally in older adults. We also discuss the available evidence for therapeutic interventions such as caloric restriction, resistance training, and senolytic and senomorphic drugs to maintain healthy metabolism with aging, focusing on data from human studies.